2015
DOI: 10.3109/09638288.2015.1070298
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Orientation to (Daily) Occupational Performance intervention leads to improvements in impairments, activity and participation in children with Developmental Coordination Disorder

Abstract: Development Coordination Disorder is a condition which has significant physical, academic and social impacts on a child and can lead to activity limitations and participation restrictions. Cognitive Orientation to Daily Occupational Performance is an approach which uses cognitive-based strategies to improve performance of specific tasks based on child chosen goals. The intervention program had a positive effect on self-perceived levels of performance which may lead to changes in quality of life. Parents felt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 31 publications
3
68
0
Order By: Relevance
“…Engaging in similar occupations can provide the opportunity to share individual strengths, contribute to others learning and in turn foster a sense of value, self-worth and competence (Hammell, 2014;Wilcock & Hocking, 2015). Mandich, Polatajko and Rodger (2003) and Thornton et al (2015) confirmed that providing education to families as part of an intervention decreases their sense of isolation and empowers parents to help their child develop an understanding of the condition and how it affects their daily lives. The crucial role of parental involvement is highlighted within the CO-OP literature to encourage children to apply what they learn during intervention sessions to other tasks, resulting in generalisation and transfer of skills (Dunford, 2011;Zwicker et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 80%
See 2 more Smart Citations
“…Engaging in similar occupations can provide the opportunity to share individual strengths, contribute to others learning and in turn foster a sense of value, self-worth and competence (Hammell, 2014;Wilcock & Hocking, 2015). Mandich, Polatajko and Rodger (2003) and Thornton et al (2015) confirmed that providing education to families as part of an intervention decreases their sense of isolation and empowers parents to help their child develop an understanding of the condition and how it affects their daily lives. The crucial role of parental involvement is highlighted within the CO-OP literature to encourage children to apply what they learn during intervention sessions to other tasks, resulting in generalisation and transfer of skills (Dunford, 2011;Zwicker et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 80%
“…Broader literature on this topic reinforces the importance of child-chosen goals which provides the opportunity for children to develop autonomy and contributes to the building of intrinsic motivation that is required to persist in task engagement (Case-Smith, 2015;Poulsen, Ziviani & Rodger, 2006). Dunford (2011) and Thornton et al (2015) suggest that opportunities for socialisation and peer support are increased when groups of children share similar goals. Hammell (2014) confirmed that a sense of connectedness develops when doing and learning occupations with others and through that connectedness, occupations come to have meaning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the articles focussed on children who fit the criteria for a diagnosis of DCD, were aged between 5 and 12 years and had received intervention using the task‐oriented approaches of the Cognitive Orientation to daily Occupational Performance (Missiuna et al ., ; Polatajko & Mandich, ; Polatajko, Mandich, Miller & Macnab, ; Polatajko et al ., ). Two of the studies conducted daily sessions over a period of 2 weeks (Dunford, ; Zwicker et al ., ) and three of the studies conducted weekly sessions, over seven, ten and twenty weeks (Chan, ; Green, Chambers & Sugden, ; Thornton et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…All studies reviewed were explicit in stating that the purpose of their research was to investigate the effectiveness of a CO‐OP approach when delivered in a group format to children with DCD (Chan, ; Dunford, ; Thornton et al ., ; Zwicker et al ., ). The fifth study conducted by Green et al .…”
Section: Resultsmentioning
confidence: 99%